Effectiveness of Partograph Use In Decision Making By Midwives - Larasati, Timmy; Kanathasan, Jayasree S. (STIKes Alifah Padang, 2024)
The high Maternal Mortality Rate (MMR) is a major issue for health care. A single one of them is in labor. The most frequent reasons of this process include problems, obstructed labor, and obstetric hemorrhage. This can be identified by applying Partograph to clinical decision-making in an attempt to identify labor issues. Medical professionals can therefore take the proper measures. The purpose of this study is to evaluate how well midwives at the Independent Midwife Practice in West Pasaman Regency use Partograph when making clinical decisions. Qualitative descriptive research is the methodology employed. Using a purposive sampling strategy, the sample size for this study was determined to be up to 6 respondents, comprising 5 core informants and 1 key informant. The outcomes The study's findings offer details on the Partograph usage that midwives at the Independent Midwife Practice in West Pasaman Regency perform, and they are deemed to be beneficial. by examining the midwives' proficiency with Partograph, which is excellent and ideal for delivering labor care. Additionally, based on the usage of partographs, midwives at the Independent Midwife Practice in West Pasaman Regency make very effective clinical decisions. Additionally, the lack of AKI recording during the previous few years aids in examining midwives' comprehension of what and how clinical decision making is carried out.